2024
DOI: 10.1039/d3ob01447a
|View full text |Cite
|
Sign up to set email alerts
|

Microbial alcohol dehydrogenases: recent developments and applications in asymmetric synthesis

Anju Chadha,
Santosh Kumar Padhi,
Selvaraj Stella
et al.

Abstract: In this review article, recent developments and applications of microbial alcohol dehydrogenases are summarized by emphasizing notable examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 143 publications
0
1
0
Order By: Relevance
“…Alcohol dehydrogenases (ADHs), belonging to the oxidoreductase class of enzymes, catalyze the production of alcohols and their oxidation to the corresponding aldehydes or ketones [1,2]. They are ubiquitous in all three domains of life and are classified into three groups based on their sizes: short-chain (group I), medium-chain (group II), and long-chain (group III) ADHs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol dehydrogenases (ADHs), belonging to the oxidoreductase class of enzymes, catalyze the production of alcohols and their oxidation to the corresponding aldehydes or ketones [1,2]. They are ubiquitous in all three domains of life and are classified into three groups based on their sizes: short-chain (group I), medium-chain (group II), and long-chain (group III) ADHs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Redox biocatalysis requires a cofactor to complete the redox cycle. The cofactor is reduced, or oxidised, according to the reaction type [ 22 , 37 ]. There are two types of cofactors for ADH, nicotinamide adenine dinucleotide non-phosphorylated (NADH/NAD + ) and its phosphorylated form (NADPH/NADP + ; see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the reaction can be judiciously manipulated by altering the reaction conditions, such as varying the solvent to yield excess R or S alcohol products from corresponding ketones [ 58 , 59 ]. Along with solvent, temperature and pH, play a significant role in achieving the desired enantiomeric conversion [ 22 , 37 , [60] , [61] , [62] , [63] , [64] ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such examples are scarce and mostly involve the combination of laccases with RLi compounds, [26,27] with no reported instances to date of synergistic combination between RLi reagents and enzymes for the development of multi-step stereoselective processes. Consequently, and trying to finish with this discontinuity in the design of stereoselective chemoenzymatic protocols, we decided to focus our interest in exploring the potential combination of organolithium reagents with alcohol dehydrogenases (ADHs), enzymes capable of catalyzing prochiral ketone bioreduction processes, [28][29][30][31] that have previously demonstrated high compatibility with a wide array of chemical reagents and catalysts. [32] Encouraged by previous results achieved by our research group in the stoichiometric addition of RLi to nitriles for their chemoselective and fast conversion into the corresponding prochiral ketones (working under neat conditions, at room temperature and in the absence of protecting atmosphere), [33][34][35][36][37][38][39][40] we have devised the chemoenzymatic sequence presented in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%